IMPACT OF CLINICAL SKILL LAB ON STUDENTS’ LEARNING IN PRECLINICAL YEARS - Ali, Liaqat; Nisar, Sabina; Ghassan, Ayesha; Khan, Saadat Ali (Journal of Ayub Medical College Abbottabad, 2011)
Background: As 1st year students have no prior training in handling and facing patients, Clinical Skill Lab (CSL) is the most suitable place to avoid direct doctor/patient interaction. The objective of this study was to evaluate the performance of recently established CSL and its impact on student learning in basic science subjects. Methodology: This study was carried out at the Departments of Physiology and Medical Education, Foundation University Medical College Islamabad, from January to October 2012. In this observational study, 150 of 1st year students were divided into 5 batches. Each batch attended clinical skill lab once a week. Each batch was subdivided into 6 batches of 5 students each to be facilitated by one postgraduate trainee from clinical subjects. Overall supervision was done by a consultant of status of Assistant Professor qualified to teach Medicine, Surgery and/or Physiology. Sessions were conducted for 2 hours daily (6 days a week) in which after an initial briefing, students were taught the communication skills, clinical skills and art of history taking and physical examination. Clinical integration of various modules taught in 1st year, i.e., skin, muscle and skeletal system (SMS), upper limb and breast, immunity and haematology, respiratory and cardiovascular modules was done from January to October 2012. Methods of teaching involved large group interactive sessions, small group interactive sessions, self-directed learning, tutorials, revision on computer and recordings of sessions given to students on flashes. Multiple choice questions and observed structured clinical examination were the main assessment tools. Combined assessment of 2 consecutive modules was done at the end of 2nd module making a total of 3 assessments for 1st year. Absentees were included in failures in view of impact of end of modules examinations on overall final assessment. Results: More than 73% students passed examination of clinical skills securing more than 50% marks in each module. Overall impact of CSL was also seen in the subjects of Anatomy and Physiology. Result of purely anatomy SMS and breast modules increased from 64% (year 2011 class) to 79% (year 2012 class). Result of purely Physiology modules (Immunity and Haematology) increased from 77% (year 2011 class) to 94% (year 2012 class). Similarly Respiratory and Cardiovascular modules result improved from 68% to 90.5%. Conclusion: The performance of CSL in imparting clinical skills, communication skills, history taking and physical examination was satisfactory. The experience of integrating clinical teaching with basic sciences not only improved students’ clinical experience reflected by evaluation, but was also rewarding in improving the results of various modules related to anatomy and physiology. Keywords: Clinical skill lab, Module, Integration, Curriculum, Medical Education, Physiology teaching